2022
DOI: 10.12928/telkomnika.v20i5.21818
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human resource analytics using machine learning algorithms

Abstract: Employee attrition is one of the most significant business issues in human resource (HR) analytics. This research aims to identify the most critical elements that contribute to employee attrition. Businesses operate heavily on employee training in order to maximize the returns they will offer to the company in the future. By utilizing the employee information value concept, it has been discovered that employee features such as overtime, the total number of projects and job level have a significant impact on at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The decision tree method is a method used to make a decision based on a rule. (Alsaadi, Khlebus, & Alabaichi, 2022) This method is also called a decision tree. (Muñoz-Rodríguez, Alonso, Pessoa, & Martín-Lucas, 2023) This method will be used to classify data on prospective students who are interested in studying at Labuhanbatu University.…”
Section: Methodsmentioning
confidence: 99%
“…The decision tree method is a method used to make a decision based on a rule. (Alsaadi, Khlebus, & Alabaichi, 2022) This method is also called a decision tree. (Muñoz-Rodríguez, Alonso, Pessoa, & Martín-Lucas, 2023) This method will be used to classify data on prospective students who are interested in studying at Labuhanbatu University.…”
Section: Methodsmentioning
confidence: 99%
“…The research method used for determining people's interest in the Telkomsel card is the decision tree method. Method Decision tree is a construction method that is usually used as a regression and classificatio (Alsaadi, Khlebus, & Alabaichi, 2022). n this study the decision tree method was used as a method for data classification.…”
Section: Methodsmentioning
confidence: 99%
“…Utilizing classification algorithms for attrition prediction, the study identified decision trees as the most accurate method. Machine learning, particularly Random Forest, outperformed others, aiding HR in predicting employee attrition effectively [7].…”
Section: Related Workmentioning
confidence: 99%